Study of Information Systems in Financial Administration within the Regional Secretariat of Bontang City - Yovanov Joshua Parulian; Anissa Yuniar Larasati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research seeks to examine the effectiveness and contribution of information systems in managing financial administration at the Regional Secretariat of Bontang City, with a particular focus on their role in facilitating the monitoring, validation, and documentation of financial accountability reports (Surat Pertanggungjawaban / SPJ). The study adopts a qualitative descriptive methodology, with data gathered through structured interviews, direct observations, and document reviews involving key personnel responsible for regional financial management. Data analysis is conducted using the DeLone and McLean Information Systems Success Model, which assesses system quality, information quality, service quality, system utilization, user satisfaction, and overall benefits. The findings reveal that the Regional Government Information System of the Republic of Indonesia (SIPD RI) has effectively standardized financial recording and reporting procedures, although it remains limited in supporting internal monitoring of financial accountability reports. To address this gap, the Secretariat Financial Administration Monitoring System (SIMPANSE) functions as a complementary system that enhances the efficiency of SPJ supervision, reinforces internal control mechanisms, and improves transparency and accountability in financial administration. This study highlights the critical role of internal support systems in maximizing the performance and success of regional government information systems.